Submandibular Lateral Ectopic Thyroid Tissue: Ultrasonography, Computed Tomography, and Scintigraphic Findings. (8th November 2015) - Çeliker, Metin; Beyazal Çeliker, Fatma; Turan, Arzu; Beyazal, Mehmet; Beyazal Polat, Hatice
Abstract : Ectopic thyroid can be encountered anywhere between the base of tongue and pretracheal region. The most common form is euthyroid neck mass. Herein, we aimed to present the findings of a female case with ectopic thyroid tissue localized in the left submandibular region. A 44-year-old female patient, who underwent bilateral subtotal thyroidectomy four years ago with the diagnosis of multinodular goiter, was admitted to our hospital due to a mass localized in the left submandibular area that gradually increased in the last six months. Neck ultrasonography, contrast-enhanced computed tomography, and scintigraphic examination were performed on the patient. On thyroid scintigraphy with Tc-99m pertechnetate, thyroid tissue activity uptake showing massive radioactivity was observed in the normal localization of the thyroid gland and in the submandibular localization. The focus in the submandibular region was excised. Pathological examination of the specimen showed normal thyroid follicle cells with no signs of malignancy. The submandibular mass is a rarely encountered lateral ectopic thyroid tissue. Accordingly, ectopic thyroid tissue should also be considered in the differential diagnosis of masses in the submandibular region.